A network analysis of post-traumatic stress among youth aging out of the foster care system. (September 2022) - Elise Barboza, Gia; Valentine, Romello
Highlights: Network analysis revealed that the DSM-IV PTSD symptom network of foster youth was dense and highly interrelated. The strongest associations in the network were found between reexperiencing and arousal symptoms. The most central symptoms in the network were emotional numbing and arousal symptoms. The relative importance network found a potential feedback loop of emotional numbing experience. Abstract: Network analysis is increasingly being used to explore interrelationships between symptoms of post-traumatic stress (PTS); nevertheless, no study to date has applied network theory to explore PTS in youth who are transitioning from foster care to independence. The present study estimated Adaptive LASSO and relative importance networks of PTS symptoms using the CIDI-PTSD Short Form (CIDI-SF) index from the Multi-Site Evaluation of Foster Youth Programs Study (2001–2010). Graph-theoretic algorithms including community detection and minimum spanning tree (MST; a unique, acyclic subnetwork with a fixed number of connections) were implemented to identify interconnected network symptom clusters. Two symptoms of emotional numbing (restricted affect and feeling detached) and two symptoms of intrusive reexperiencing (flashbacks, distressing dreams) emerged as the most important items in the network. The MST algorithm further revealed a backbone structure of PTSD that was centered on negative evaluations of the future. Feedback loops within the network were identified as well as symptoms that were highly predictive and potentially causal. Results strongly suggest that emotional numbing is a central aspect of psychopathology following experiences of complex trauma and home removal that merits special consideration in the diagnostic and treatment evaluation process of youth involved in the foster care system.